Close to consumers: How brands can foster brand loyalty within families - Janina Rebecca Kauz (Marketing Review St.Gallen, 2025)
Research shows that brands are embedded in familial consumption practices. However, it is unclear what brands can do to foster their inclusion within a practice. This article shows that brands can embed themselves in family practices by providing materials for practices, fostering extraordinary meanings in ordinary practices, and imparting competences.
Keywords: 650